2018
DOI: 10.1016/j.otsr.2018.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Patellofemoral reconstruction for patellar instability with patella alta in middle-aged patients: Clinical outcomes

Abstract: IV. Retrospective case series study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 25 publications
0
23
0
Order By: Relevance
“…65 Overall, operative intervention has been shown to result in adequate patient outcomes, satisfaction, and postoperative stability. 16,18,58,63,68,88 Improved knowledge about pathologies involving the patellofemoral joint has been a major driving force for tailored management. 90 With the increase in treatment approaches and research on patellar instability, it is imperative to analyze the types and quality of these investigations to determine the driving factors for current and future clinical practice.…”
mentioning
confidence: 99%
“…65 Overall, operative intervention has been shown to result in adequate patient outcomes, satisfaction, and postoperative stability. 16,18,58,63,68,88 Improved knowledge about pathologies involving the patellofemoral joint has been a major driving force for tailored management. 90 With the increase in treatment approaches and research on patellar instability, it is imperative to analyze the types and quality of these investigations to determine the driving factors for current and future clinical practice.…”
mentioning
confidence: 99%
“…The PFJ is a unique and complex structure [5], which is stabilized by a complex multivariate relationship of osseous joint geometry and force vectors generated by the capsuloligamentous stabilizers and quadriceps femoris [6]. Patellar instability (PI) is frequently caused by pathological changes involving PFJ stabilizers, which increase the likelihood of lateral patellar dislocation and early OA [8].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, PI is related to trochlear dysplasia [8]. Schottle et al demonstrated that trochlear dysplasia of the femur is a predisposing factor for recurrent PI [9].…”
Section: Introductionmentioning
confidence: 99%
“…An increased tibial tuberosity-trochlear groove (TTTG) distance measured on CT scan is an important factor for patellar instability and is clinically used for defining the indications for the medialising tibial tubercle osteotomy (TTO) [1][2][3] . It approximates the amount of lateralisation of the patellar tendon insertion by using the apex of the tibial tuberosity as the landmark for the location of the patellar tendon.…”
Section: Introductionmentioning
confidence: 99%